Effect of storage time and conditions on the quality characteristics of 'Moroccan Picholine' olive oil. (January 2022) - El Yamani, Mohamed; Sakar, El Hassan; Boussakouran, Abdelali; Rharrabti, Yahia
Abstract: The influence of extraction system and both storage time and conditions on quality characteristics of 'Moroccan Picholine' virgin olive oil (VOO) was investigated. Results from ANOVA analysis showed that the storage time largely affected the most of VOO characteristics (peroxide value, K270, chlorophylls, carotenoids and total phenols). The K232 variability was due to both extraction system and storage time. The free fatty acids were mostly dependent on extraction system. Moreover, we observed that increasing the storage time provoked a slight but significant accumulation in free fatty acids and higher values for oxidation indices. The highest increment rates were recorded in the first months of storage for the peroxide value and from the 6th month onwards for K232 and K270. For carotenoids, chlorophylls and total phenols, we noticed dramatic losses after twelve months of storage. Among extraction systems, the two-phase centrifugation system kept the good VOO quality and displayed the lowest values of free fatty acids, peroxide value, K232, and K270, and the greatest records for carotenoids and total phenols contents. It has been also revealed that VOO stored in the dark at 4 °C maintained the best quality indices. Exposure of VOO to light and ambient temperatures caused substantial deterioration in quality parameters. Principal component analysis (PCA) explained about 91% of total variability: 77 and 14% for PC1 and PC2, respectively. Storage time fitted the variability of PC1, while extraction system caused the variability on PC2. Correlation studies showed a clear association of oxidation indices with antioxidant compounds. Highlights: The stability of virgin olive oil (VOO) during storage was discussed. Results evidenced the factors and conditions that further promote VOO degradation. Storage promoted VOO hydrolysis and oxidation according to its antioxidant content. VOO Oxidation is favored by high temperatures and exposure to light. Phenols and carotenoids have a crucial role against the VOO deterioration.